The Visual Discourse of the Roma Community in the Spanish Press: Multimodal Critical Analysis of Key Journalistic Images - Oleaque-Moreno, Joan M.; Castellanos-Pineda, Patricia; Torralba-Mesas, Desirée (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This article reviews the visual representation of the roma community in the Spanish press. It examines the first decade of the 21st century, a key period marked by the arrival of migrants, including those from this ethnic group, and by the role of mainstream media. A multimodal critical discourse analysis (MCDA) is applied to images from two major Spanish newspapers. The results reveal non-obvious meanings embedded in the content of these images, allowing for a deeper understanding of the development of the Roma community’s situation, based on the visual treatment they receive.